Electrophilically Activated Nitroalkanes in Reactions With Carbon Based Nucleophiles - Aksenov, Nicolai A.; Aksenov, Alexander V.; Ovcharov, Sergei N.; Aksenov, Dmitrii A.; Rubin, Michael (Frontiers in Chemistry, 2020)
Unusual reactivity of nitroalkanes, involving formation of aci-forms (nitronic acids or nitronates) and their subsequent interaction with carbon-based nucleophiles, is surveyed in this review